Kepastian Hukum Kepemilikan Senjata Api Bagi Masyarakat Sipil Dalam Konteks Negara Hukum (Rechtsstaat) - ALFI, Muhammad Alfisyahri Subakti (LPPM Universitas Putera Batam, 2024)
In the context of a rule of law, the presence of firearms in civil society is a complex and sensitive issue. Ownership of firearms by civilians can pose a significant threat to the security and stability of the country. So far the regulations governing the presence of firearms in the hands of civil society have not been seen to provide maximum results, as the supervision and control of firearms is still very loose, causing concern among the community if it is related to the context of a legal state which guarantees that the rights of the community will be protected by the law itself. This research aims to analyze the legal framework that regulates the urgency of ownership of firearms by civil society in the context of a rule of law state. The research method used is normative research by analyzing legal documents, including constitutions, laws, regulations and court decisions regarding firearms ownership. The research results show that the urgency of owning firearms for civil society in the context of a rule of law is strongly influenced by considerations of public security, human rights and social justice. Although some states may allow firearm ownership as part of a constitutional right, this research highlights the need for strict regulation and effective law enforcement to ensure that firearm ownership does not threaten the safety and well-being of society as a whole.